Analisis Kemudahan Interaksi Pengguna dengan Disabilitas Motorik pada Aplikasi Grab Menggunakan Fitts’law dan Task Based Performance (Studi Kasus LKS Sahabat Kita) - Sofianingsih, Leny; Cahyono, Taufiq Agung (Lembaga Intelektual Muda (LIM) Maluku, 2026)
This study aims to evaluate the ease of interaction for users with motor disabilities on the Grab application using Fitts' Law and Task-Based Performance methods. The study applied a quantitative approach involving 35 people with motor disabilities at LKS Sahabat Kita in Tulungagung Regency as respondents. Data were collected through observation, measuring task completion times, recording success and error rates, and analyzed using Fitts' Law to measure interaction difficulty and Task-Based Performance to evaluate interface effectiveness. The results showed that the Grab application has a low level of interaction difficulty with an Index of Difficulty (ID) value of 1.36–2.00. This finding is supported by a high task completion success rate (85.71%–100%) and a relatively short task completion time, indicating that most application features can be operated well by users with motor disabilities. However, several interface elements were still found to potentially hinder interaction and therefore require improvements to improve accessibility. This study contributes as an empirical basis for the development of application interfaces that are more inclusive and user-friendly for users with motor disabilities.